2016
DOI: 10.1111/jam.13316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic loading rate on hydrogen and volatile fatty acid production and microbial community during acidogenic hydrogenesis in a continuous stirred tank reactor using molasses wastewater

Abstract: Microbial information on hydrogen and VFA production can be useful to design and operate for acidogenic hydrogenesis using high strength molasses wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…SCFAs were negatively correlated with Proteobacteria and Tenericutes , but positively correlated with Bacteroidetes and Firmicutes . In line with our results, other investigators have documented that SCFAs are positively correlated with Firmicutes ( Bacillales , Sporolactobacillus and Lactobacillus ) [33]. Moreover, it has been revealed that while Proteobateria decreased, butyrate-producing bacteria ( Lactobacillus and Prevotella ) increased in fermented soybean meal fed piglets, implying that Proteobateria and butyrate concentration have negative correlation [34].…”
Section: Discussionsupporting
confidence: 91%
“…SCFAs were negatively correlated with Proteobacteria and Tenericutes , but positively correlated with Bacteroidetes and Firmicutes . In line with our results, other investigators have documented that SCFAs are positively correlated with Firmicutes ( Bacillales , Sporolactobacillus and Lactobacillus ) [33]. Moreover, it has been revealed that while Proteobateria decreased, butyrate-producing bacteria ( Lactobacillus and Prevotella ) increased in fermented soybean meal fed piglets, implying that Proteobateria and butyrate concentration have negative correlation [34].…”
Section: Discussionsupporting
confidence: 91%
“…It has been documented that Ruminococcaceae can produce acetate [42], and Lactobacillus is able to produce lactate which can be utilized by the bacteria belonging to the Clostridial cluster XIVa to produce butyrate [43]. Besides, the contents of acetate, butyrate, and propionate have been reported to be positively correlated with lactic acid bacteria such as Bacillales , Sporolactobacillus , and Lactobacillus [35]. Thus, our present data, which shows the correlations between bacteria species and SCFAs contents, may provide some implications for understanding the association between intestinal microbiota composition and SCFAs production after severe burn injury.…”
Section: Discussionmentioning
confidence: 99%
“…An agglomeration step will filter out noise induced by these phylogenetic similarities, while revealing conserved interactions at higher taxonomic levels. As an example, Yun and Cho ( 2016 ) visualized how specific orders correlated to environmental factors and showed how different communities were associated with certain metabolites. If researchers are interested in highly conserved cross-feeding interactions (e.g.…”
Section: Network Interpretation Benefits From Data Integrationmentioning
confidence: 99%